Claisen type Condensation of Methyl Ketones with Carbimidothioates: A New Gateway for the Synthesis of β-Enaminones - Swaroop, Toreshettahally R.; Rangappa, Kanchugarakoppal S.; Torun, Lokman (WILEY-V C H VERLAG GMBH, 2021)
Carbimidothioates are synthesized by the reaction of Grignard reagents or heteroaryl lithium compounds with arylisothiocyanates followed by treatment with methyl iodide. Further, application of these intermediates in the synthesis of beta-enaminones by their condensation with methyl ketones in the presence of sodium hydride in DMF is reported. This method offers a new gateway for the synthesis of beta-enaminones, which are important building blocks in synthetic organic chemistry.
Keywords: carbimidothioates; beta-enaminones; grignard reagents; methyl ketones; organolithium compounds; CATALYZED CYCLIZATION; BOND FORMATION; ALPHA,BETA-UNSATURATED KETONES; ALPHA-OXODITHIOESTERS; XANTHATE ESTERS; ACID; ISOCYANIDES; EFFICIENT; BASE; FUNCTIONALIZATION; Chemistry